Visual system involvement in selected zoontic diseases. III. Cysticercosis T. solium - Kocięcki, Jarosław; Kocięcka, Wanda (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Cysticercosis of visual system is a serious clinical problem. Cysticercosis (cysticercus cellulose) may cause damage to different structures of this system, leading sometimes to dangerous consequences (phthisis and total blindness). Involvement of visual system may coexist with cysticercosis of central nervous system. In current paper we present parasytologic and epidemiologic aspects, as well as clinical pathology of T. solium cysticercosis with special attention directed to lesions within visual system. Current laboratory methods (immuno- and radiologic) indispensable for diagnosis of cysticercosis, as well as outline of therapy (pharmacological and surgical), are also presented.